Estudo do estado nutricional, nível de atividade física e perfil lipídico de idosos participantes de grupos de convivência - Cezaro, Jéssica Cristina de (2017)
The results of the evaluation of the lipid profile of the elderly tend to be associated with overweight and obesity for sedentarism, suggesting alterations of the lipid profile in relation to the body mass index. The objective of the first study was to evaluate the relationship between the lipid and glycemic profile and the body mass index of the elderly. This research is a cut of the research conducted in 2011 by the University of Passo Fundo, Rio Grande do Sul. The groups of elderly included in this study were the Regional Center for Studies and Activities for the Elderly and the Department of Support for the Third Age. Participated 65 elderly and the variables measured were weight and height, fasting glycemia, total cholesterol, Low Density Lipoprotein cholesterol, High Density Lipoprotein cholesterol and triglycerides. The data were analyzed using descriptive statistics and the Spearman correlation coefficient for a significance level of p≤0.05. For the overweight group, total cholesterol presented a positive correlation with Low Density Lipoprotein (p <0.001). In the eutrophic group there was a positive correlation between glucose and triglycerides (p = 0.005) and between total cholesterol and Low Density Lipoprotein (p <0.001). The study shows that glycemia and triglycerides are directly related among eutrophic, and that total cholesterol and Low Density Lipoprotein in both groups indicate that elevation of o ne changes the other. For the second study, the objective was to evaluate the relationship between nutritional status and physical activity level of the elderly. The work developed is also a cut of the research produced at the University of Passo Fundo, whose elderly were part of the cohabitation groups previously mentioned. In this research, 75 elderly were included, and the variables collected were weight, height, tricipital skin fold, subscapular cutaneous fold, waist circumference and hip circumference. To evaluate the frequency of physical activities, section four of the International Physical Activity Questionnaire was used. The data were analyzed using the chi-square, Mann-Whitney, Kruskal-Wallis and Spearman correlation tests at a significance level of p≤0.05. Regarding the performance of physical activities and family income, the chisquare test showed significance among the group receiving three minimum wages or more (p = 0.035). The Mann-Whitney test showed differences between sex and tricipital skin fold (p <0.001) and between waist-hip ratio (p <0.001). Regarding the frequency of physical activity, the subscapular skinfold presented significance (p = 0.026). Likewise, subscapular cutaneous fold (p = 0.001) and tricipital cutaneous fold (p = 0.001) showed differences in body mass index. Despite weekly physical activities, the majority of the elderly face excess body weight, and older people with greater skinfold measurements have a higher body mass index. It is also verified that income is an important factor for the accomplishment of these activities.